Catastrophizing and acceptance are mediators between insomnia and pain intensity—an SQRP study of more than 6,400 patients with non-malignant chronic pain conditions - Gerdle, Björn; Dragioti, Elena; Rivano Fischer, Marcelo; Dong, Huan-Ji; Ringqvist, Åsa (Frontiers in Pain Research, 2023)
Background: There are associations between sleep problems (insomnia) and chronic pain.Chronic pain and insomnia/insufficient sleep quality have several symptoms and features in common. Although they appear to have a bidirectional relationship, understanding how they interact via mediators and how moderators influence this relationship need further study.Aims: This large clinical registry-based cohort study (N = 6 497) investigates important mediators between insomnia and pain intensity using advanced path analysis in a crosssectional sample of chronic pain patients. In addition, we investigate whether some background variables were moderators of the identified important paths and the correlation patterns for insomnia and pain intensity in relation to the mediators.This study includes a cohort of adult chronic non-cancer pain patients from the Swedish Quality Registry for Pain Rehabilitation (SQRP) with Patient-Reported Outcome Measures (PROMs) data (2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016). The PROMs cover a patient's background, pain aspects, psychological distress, pain-related cognitions, activity/participation, and healthrelated quality of life variables. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to explore the direct and indirect (via mediators) relationships between insomnia and pain intensity at baseline.In this cohort, insomnia had a prevalence of 62.3%, and both direct and indirect mediating paths were present for the insomnia-pain intensity relationship. All mediating effects taken together were weaker than the direct effect between insomnia and pain intensity.The mediating effects via catastrophizing and acceptance showed the strongest and equal mediating paths, and mediating effects via fear-avoidance were the second strongest.